The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s13592-019-00699-4
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition in honey bees (Apis mellifera L.): the role of body size dimorphism in drones

Abstract: Previous experimental studies demonstrated that small drones (SD) had lower paternity share since they were not successful in mating with queens as large drones (LD) in the mating arena. However, it remains unclear whether spermatozoa of SD can compete in vivo with those of LD if SD have mating opportunity. We, therefore, tested the spermatozoal competitiveness of SD against LD by instrumentally inseminating the queens with varying proportions of semen from LD and SD. Sister queens from a Buckfast colony and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Gencer and Kahya mixed the sperm of two types of male bees of A. mellifera in different proportions for artificial insemination of queens. The paternal frequencies in the offspring of SDs were all lower than expected, while large males produced more offspring than expected [89]. Although SDs remained slightly behind LDs in regard to sperm competition, this does not imply that SDs reared in LWCs are useless.…”
Section: Body Sizementioning
confidence: 63%
See 1 more Smart Citation
“…Gencer and Kahya mixed the sperm of two types of male bees of A. mellifera in different proportions for artificial insemination of queens. The paternal frequencies in the offspring of SDs were all lower than expected, while large males produced more offspring than expected [89]. Although SDs remained slightly behind LDs in regard to sperm competition, this does not imply that SDs reared in LWCs are useless.…”
Section: Body Sizementioning
confidence: 63%
“…Although SDs remained slightly behind LDs in regard to sperm competition, this does not imply that SDs reared in LWCs are useless. In addition, the concentration of sperm in the ejaculate affects the reproductive success of drones, and evolution forces drones to produce not only plentiful but also particularly concentrated semen [89].…”
Section: Body Sizementioning
confidence: 99%
“…The concentration of sperm presented on the endophallus is predictive of a drone's reproductive success [66,67]. More concentrated sperm increase a drone's probability of getting sperm pumped through the oviducts into the spermatheca, which are then used for fertilization.…”
Section: Importance and Determinants Of Sperm Concentration And Quality To Dronesmentioning
confidence: 99%
“…Since sperm competition is likely non-existent or limited in honey bees [37], drones producing more sperm have a greater probability of fertilizing eggs. For example, sperm inseminated at higher quantities had greater paternal frequencies than sperm at lower quantities [66,67]. Additional studies found smaller drones had lower reproductive success, and they attributed this to lower sperm quantity [68].…”
Section: Importance and Determinants Of Sperm Concentration And Quality To Dronesmentioning
confidence: 99%
See 1 more Smart Citation